BathyBoat: Autonomous surface command and control for underwater vehicle networks - Brown, Hunter; Meadows, Guy; Jenkins, Liza; Shuchman, Robert A. (2010)
This paper reports the preparation of two modiﬁed Ocean-Server AUV systems and the construction of a new autonomous surface vessel (ASV) for cooperative simultaneous localization and mapping (SLAM) research at the University of Michigan (UMich). The Marine Hydrodynamics Laboratories (MHL) has designed and fabricated the new ASV BathyBoat to serve as a targeted remote sensing platform and a mobile command and control center for underwater search and survey activities performed by UMich Perceptual Robotics Laboratory (PeRL) AUVs. The ASV is outﬁtted with a suite of sensors including a RadarSonics 250 acoustic depth sensor, Garmin WAAS-enabled GPS, Honeywell HMR3300 digital compass and accelerometer, Vernier CON-BTA conductivity probe, a WHOI Micro-Modem for two-way communication with the AUVs, and other sensors discussed subsequently. Wireless data transmission from the surface offers the ability to monitor, in real-time, the state of the AUVs. In addition, updated mission objectives can be relayed, from ship or shore, through the ASV for mid- mission adjustments. Ongoing scientiﬁc and engineering research objectives are discussed, along with an overview of the new autonomous surface vessel and a summary of ﬁeld trials on the North Slope of Alaska. NSF #IIS 0746455 ONR #N00014-07-1-0791 Michigan Tech Research Institute http://deepblue.lib.umich.edu/bitstream/2027.42/65070/1/UI2010_Final.pdf